Extractive Metallurgy Division - Electrical Conductivity of Melts in the Systems NaCl-ZrCl4 and NaC1-KCL (1;1 molar) –ZrCl4 (TN) - L. J. Howell; H. H. Kellogg (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1960)
AN a previous paper' the phase diagram and vapor pressure of melts in the systems NaC1-ZrCl,, KC1-ZrCl,, and NaC1-KC1 (1:1 molar)-ZrC1, were reported. This note supplements the earlier paper with the results of electrical conductivity measurements on NaC1-ZrC1,and NaC1-KC1 (1:l molar)-ZrC1, melts. The design of the conductivity cell is shown in Fig. 1. Tungsten electrodes, A, were sealed into the Pyrex cell, C. That portion of the electrodes in contact with the melt was covered with a tight-fitting platinum cap. The electrodes were sur-